Analysis of user experience during interaction with selected CMS platforms - Miszczak, Michał; Dzieńkowski, Mariusz (Journal of Computer Sciences Institute, 2021)
The purpose of this study was assessing user experience while working with two popular CMS systems: WordPress and PrestaShop. The evaluation was done using a questionnaire and an eye tracking technique. Average task completion time, the number of fixations, the percentage of correctly completed tasks and the SUS index were used for comparisons. On the basis of the obtained results which, were collected during and after the users' interaction with a given system, it is difficult to clearly state which CMS proved to be better.